Response of Kalahari vegetation to seasonal climate and herbivory: Results of 15 years of vegetation monitoring. (16th September 2020) - Schmiedel, Ute; Jacke, Vasco; Hachfeld, Berit; Oldeland, Jens
Abstract: Questions: The arid Kalahari is prone to desertification as a result of climate change and/or land use. We analysed the effects of climatic variables and game herbivory on the vegetation composition to answer the question of how different life‐form types respond to climate, browsers and grazers as drivers of vegetation change. Location: The study was situated in the arid savanna of the South African Kalahari. Methods: Vegetation monitoring was conducted on 20 randomly selected permanent plots (100 m 2 ) within a biodiversity observatory. For each plot, individuals per species (abundance) were counted annually and grouped into eight life‐form types (annual and perennial graminoid and annual and perennial forb, geophyte, dwarf shrub, large shrub and tree). We ran generalised linear mixed models (GLMM) with abundance per life‐form type as response variable and a seasonal drought index (Standardised Precipitation–Evapotranspiration Index [SPEI]), total annual rainfall, year, density of large game and springbok as fixed effects, plot as random effect and year as random slope. Results: Seasonal SPEI and density of large game and springbok had the strongest effect on abundance per life‐form type. Annual rainfall did not show any effect. The grazing large game had positive effects on the abundance of herbaceous life forms and dwarf shrubs. The predominantly browsing springbok had negative effects on perennial forbs, dwarf shrubs and trees. Directional trends in abundance per life form over time (increase of annual and decrease of perennial graminoids and forbs, increase of large shrubs) and decrease of total annual cover suggest early stages of vegetation degradation and shrub encroachment in response to both herbivory and climate. Conclusions: Our study showed that studies aimed at understanding the dynamics of arid systems should include both variance of intra‐annual climatic conditions and herbivore density as environmental drivers, related to abundance per life‐form/strategy type to reveal their specific responses to the environment. Abstract : We analysed the effects of climatic variables and game herbivory on the Kalahari vegetation. Seasonal SPEI and herbivore density had the strongest effect on the abundance per life‐form type. Large game (grazers) had positive effects on herbaceous life forms and dwarf shrubs; springbok (browsers) had negative effects on perennial forbs, dwarf shrubs and trees. Annual rainfall had no effect.